2014
DOI: 10.1016/j.vaccine.2014.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a universal CD4 memory T cell recall peptide effective in humans, mice and non-human primates

Abstract: CD4T cells play a key role in humoral immunity by providing help to B cells, enabling effective antibody class switching and affinity maturation. Some vaccines may generate a poor response due to a lack of effective MHC class II epitopes, resulting in ineffective helper T cell activation and recall and consequently poor humoral immunity. It may be beneficial to provide a CD4T cell helper peptide with a vaccine particularly in the case of a poorly immunogenic antigen. Such a T cell helper peptide must be promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 44 publications
2
75
0
1
Order By: Relevance
“…It is also argued that this epitope also bears at least one B cell epitope (323)(324)(325)(326)(327)(328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339), however, there is only one study that has mentioned the presence of the B cell epitope [327]. In a study by Sun et al, it was shown that 50% of the B cell response generated by the OVA protein was antibody specific to the OVA323-339 epitope [327].…”
Section: Immunisation By Mannosylated Peptides Resulted In An Impairementioning
confidence: 99%
See 4 more Smart Citations
“…It is also argued that this epitope also bears at least one B cell epitope (323)(324)(325)(326)(327)(328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339), however, there is only one study that has mentioned the presence of the B cell epitope [327]. In a study by Sun et al, it was shown that 50% of the B cell response generated by the OVA protein was antibody specific to the OVA323-339 epitope [327].…”
Section: Immunisation By Mannosylated Peptides Resulted In An Impairementioning
confidence: 99%
“…In a study by Sun et al, it was shown that 50% of the B cell response generated by the OVA protein was antibody specific to the OVA323-339 epitope [327]. As the vaccine structures (G1-6) contain the CD4 epitope (OVA [323][324][325][326][327][328][329][330][331][332][333][334][335][336][337][338][339], the in vivo ability of vaccine structures (G1-9) for a T cell activation proliferation was assessed. Here, OT-II proliferating cells are considered to be activated when T cells expressing CD45.2 increase in percentage over the total parental CD4 + T cells [329].…”
Section: Immunisation By Mannosylated Peptides Resulted In An Impairementioning
confidence: 99%
See 3 more Smart Citations